Increasing exercise participation during the COVID-19 pandemic: the buffering role of nostalgia - Cho, Heetae; Wang, John Chee Keng; Kim, Sunghoon; Chiu, Weisheng (Frontiers in Psychology, 2023)
Due to the coronavirus disease 2019 (COVID-19) pandemic, people faced difficulties engaging in exercise activities as usual. As a result, there has been an increase in the demand for home exercises and online sales. However, there is little research on individuals' buying and exercise behaviors during the pandemic. Thus, this study investigated how the perceived threat of COVID-19 influences exercise participants' compensatory consumption and exercise intention through emotional responses, such as feelings of solastalgia and nostalgia. A total of 488 responses were collected from Generation Y, as individuals belonging to Generation Y are more prone to impulsive buying compared to other generations and, importantly, consider exercise a crucial component of their general well-being. Results showed that perception of COVID-19 positively influenced solastalgia and negatively affected nostalgia. Also, solastalgia had positive effects on nostalgia and online browsing, and nostalgia positively affected online browsing. Finally, this study found that online browsing positively influenced impulse buying and exercise intention, while impulse buying did not significantly affect exercise intention. This study contributes to identifying the crucial influence of emotions in decision-making and increasing the understanding of the connection between nostalgia and cognitive and emotional responses amid the COVID-19 pandemic.